Comprehensive Profile of Morbidity and Psychoactive Substances Used among the Elderly Tribal and Non-Tribal Population of the Imphal East District of Manipur, India - Sonia Yengkokpam; Natasha R. Marak; Pavana Kumar; Sunanda Nongthombam (Disease and Health Research: New Insights Vol. 2, 2024)
This present study employs correlation and regression analysis to compile a comprehensive profile of morbidity and psychoactive substance, especially referring to cigarette smoking, tobacco chewing and alcohol consumption among the elderly tribal and non-tribal populations in the Imphal East district of Manipur, India. As the elderly population is likely to increase in the future, there will be a definite shift in the disease pattern, i.e., from communicable to non-communicable. So, it is high time that the primary healthcare system gears up for the growing health needs of the elderly in an equitable, optimal, and comprehensive manner. When it comes to communicable diseases, mosquito-borne illnesses rank highly among India’s public health issues. The three most serious ones are dengue fever, chikungunya fever, and malaria. The general community’s education about preventing mosquito bites is one of the key elements of the vector-borne disease control program. The findings provide valuable insights for targeted interventions and policy formulation to address the pressing health challenges faced by the elderly in this region. Through a thorough assessment of morbidity and substance use, this study contributes to a deeper understanding of the health dynamics within the elderly population, paving the way for informed decision-making and improved healthcare strategies tailored to the needs of this vulnerable demographic group. Addressing the issue of addiction requires the implementation of diverse educational and motivational activities aimed at promoting healthier lifestyles and reducing substance use among the elderly. Thus, based on the findings of this study, it is imperative to develop comprehensive healthcare strategies and policies that prioritize the care and support of the elderly population, ensuring their overall well-being and quality of life.